Cement work at Robert and Mary Roellke's Home at 3511 E. Balch Avenue, Fresno - Watkins, Howard::::::::: (1984)
Cement mixer truck unloading into pumping machine hitched to red pick-up truck Cement mixer truck unloading into pumping machine hitched to red pick-up truck